Causes of death and prognostic factors in Thai patients with systemic lupus erythematosus - Kasitanon N. (2014)
From a cohort study of 349 Thai patients (337 females [F] and 12 males [M]) with systemic lupus erythematosus (SLE), 52 patients (51 F, 1 M) died. Their 5- and 10-year survival rates were 84.0% and 74.9%, respectively. Seventy-nine percent of deaths occurred within the first year of diagnosis. Infection contributed to 27 deaths (51.9%). The lung and the urinary system were the 2 most common sites of infection. There were 18 SLE-related deaths (34.6%), and 7 non-SLE related deaths (13.5%). In a multivariate analysis of all causes of death, serositis, hematologic abnormality, central nervous system (CNS) and renal involvement were significantly associated with poor survival, while photosensitivity and arthritis were significantly associated with longer survival. Among SLE-related death, serositis and CNS involvement were significantly associated with poor survival, and arthritis was associated with longer survival. In conclusion, infection was the most common cause of death in Thai SLE patients. CNS and visceral involvement were associated with a poor outcome.